Human Security Implications of Foreign Military Bases in Djibouti - Onor, Kester C (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2023)
The principles of sovereignty and non-interference have historically shaped China's foreign policy, serving as fundamental tenets to safeguard the nation from external interventions, particularly during and after the Cold War. However, in recent times, there has been a noticeable shift in China's foreign policy as it embarks on an unprecedented expansion of its military presence beyond its borders. This shift is exemplified by the establishment of a permanent military base in Djibouti, situated in the Middle East and North African (MENA) region, which China refers to as "support facilities" or "logistical facilities." This marks China's inaugural venture into maintaining a permanent military presence outside its territorial boundaries. This study delves into the motivations behind China's adjusted foreign policy stance and examines the implications of this new approach on human security. While acknowledging the critical human insecurity implications associated with China's military presence in Djibouti, the analysis reveals a multifaceted strategy encompassing economic, political, ideological, and security interests. This strategic move positions China as a significant global player, shaping its role on the world stage.